Unlike Kt, high Kt/V is associated with greater mortality: The importance of low V - Rafael Perez-Garcia; Maite Jaldo; Roberto Alcázar; Patricia de Sequera; Marta Albalate; Marta Puerta; Mayra Ortega; M. Caridad Ruiz; Elena Corchete (Nefrología (English Edition), 2019)
Introduction: Kt/V has been used as a synonym for hemodialysis dose. Patient survival improved with a Kt/V > 1; this target was subsequently increased to 1.2 and 1.3. The HEMO study revealed no significant relationship between Kt/V and mortality. The relationship between Kt/V and mortality often shows a J-shaped curve. Is V the confounding factor in this relationship? The objective of this study is to determine the relationship between mortality and Kt/V, Kt and body water content (V) and lean mass (bioimpedance). Methods: We studied a cohort of 127 prevalent hemodialysis patients, who we followed-up for an average of 36 months. Kt was determined by ionic dialysance, and V and nutrition parameters by bioimpedance. Kt/V, Kt corrected for body surface area (Kt/BSA) and target Kt/BSA were calculated. The mean data from 18,998 sessions were used as hemodialysis parameters, with a mean of 155 sessions per patient. Results: Mean age was 70.4 ± 15.3 years and 61% were male; 76 were dialyzed via an arteriovenous fistula and 65 were on online hemodiafiltration. Weight was 70.6 (16.8) kg; BSA 1.8 (0.25) m2; total body water (V) 32.2 (7.41) l and lean mass index (LMI) 11.1 (2.7) kg/m2. Mean Kt/V was 1.84 (0.44); Kt 56.1(7) l and Kt/BSA 52.8 (10.4) l. The mean target Kt/BSA was 49.7 (4.5) l. Mean Kt/BSA − target Kt/BSA + 6.4 (7.0) l. Patients with a higher Kt/V had worse survival rates than others; with Kt this is not the case. Higher Kt/V values are due to a lower V, with poorer nutrition parameters. LMI and serum albumin were the parameters that best independently predicted the risk of death and are lower in patients with a higher Kt/V and lower V. Conclusion: Kt/V is not useful for determining dialysis doses in patients with low or reduced body water. Kt or the Kt/BSA are proposed as an alternative. Resumen: Introducción: El Kt/V se ha usado como sinónimo de dosis de hemodiálisis. La supervivencia de los pacientes mejoraba con un Kt/V > 1; este objetivo posteriormente fue elevado a 1,2 y a 1,3. En el estudio HEMO no se demostró una relación significativa entre Kt/V y la mortalidad. La relación Kt/V y mortalidad con frecuencia es una curva en «J». ¿Es la V el factor de confusión de esa relación? El objetivo de este estudio es buscar la relación de la mortalidad con el Kt/V, Kt y con el contenido de agua corporal (V) y masa magra (bioimpedancia). Métodos: Se ha estudiado una cohorte de 127 pacientes prevalentes en hemodiálisis seguidos durante una media de 36 meses. Se determinó el Kt por dialisancia iónica y la V y parámetros de nutrición mediante bioimpedancia. Se ha calculado el Kt/V y el Kt alcanzado corregido para superficie corporal (Ktsc) y el Ktsc objetivo. Como parámetros de hemodiálisis se ha utilizado la media de los datos de 18.998 sesiones, con una media de 155 sesiones por paciente. Resultados: La edad media fue 70,4 (15,3) años y un 61% eran hombres; 76 se dializaban mediante fístula arteriovenosa y 65 estaban en HDF-OL. Peso: 70,6 (16,8) kg; superficie corporal: 1,8 (0,25) m2; agua corporal total: 32,2 (7,4) l; índice de masa magra (LTI): 11,1 (2,7) kg/m2. El Kt/V medio fue 1,84 (0,44); Kt: 56,1 (7) l, y el Ktsc, 52,8 (10,4) l. El Ktsc objetivo medio era de 49,7 (4,5) l. La media del Ktsc – Ktsc objetivo: +6,4 (7,0) l. Los pacientes con un Kt/V mayor tienen peor supervivencia que el resto. Con el Kt no existe esta relación. Los Kt/V mayores se deben a una V menor, con peores parámetros de nutrición. La albúmina sérica y el LTI son los parámetros que se relacionan con el riesgo de muerte de forma independiente y son menores en los pacientes con mayor Kt/V y menor V. Conclusión: El Kt/V no es útil para determinar la dosis de diálisis en pacientes con un agua corporal pequeña o disminuida. Se propone el Kt o el Ktsc como alternativa. Keywords: Kt/V, Kt, Hemodialysis, Mortality, Nutrition, Total body water, Palabras clave: Kt/V, Kt, Hemodiálisis, Mortalidad, Nutrición, Agua corporal total